Pain, Injury, Mortality: Police Confront Critical Incidents - Werling, Robert; Pereira, Amanda; Morris, Gregory; Randol, Blake (International Journal of Criminology and Sociology, 2018)
Previous research has shown that the law enforcement occupation is a dangerous profession that has the highest violent victimization rate in the United States (Fridell, Faggiani, Taylor, Brito, & Kubu, 2009). This descriptive study aims to add to the growing body of literature on victimization of police officers by answering the central research question: What are the characteristics of victimization incidents of on-duty law enforcement officers? Specific demographics of interest include; sex of the officer, method of harm used against the officer, incident location, and responding call type. A content analysis was performed on news articles reporting incidents of on-duty law enforcement fatalities and injuries (n=50), in which characters gathered from the articles were recoded to numbers for quantitative analysis. Analysis of data suggests that male officers are more likely to be victimized while on-duty. Gunfire is the method of harm most likely used to victimize officers. A roadway is the location where an incident of victimization will most likely occur, during other types of calls beyond warrant services, traffic stops, domestic disturbances, and suspicious persons. This research can lead to future more detailed research and causal analysis.